2018
DOI: 10.1039/c7sc03553e
|View full text |Cite
|
Sign up to set email alerts
|

Epimerization-free access to C-terminal cysteine peptide acids, carboxamides, secondary amides, and estersviacomplimentary strategies

Abstract: We present a convenient method for the diversification of peptides bearing cysteine at the C-terminus that proceeds to form a variety of carboxylic acid, carboxamide, 2° amide, and ester terminated peptides without any detectable epimerization of the α-stereocenter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 76 publications
(45 reference statements)
1
11
0
Order By: Relevance
“…Therefore, a few representative alcoholic cosolvents were evaluated. We previously found that i -PrOH reacted more slowly than primary alcohols, 9 so we reasoned that it would minimize ester byproduct formation. Gratifyingly, in the presence of NaSPh, these conditions reduced byproduct formation to 6% of the ester ( 15c ), which was indeed readily separated from the elongated acid LYRAGLRAYP ( 15a , entry 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a few representative alcoholic cosolvents were evaluated. We previously found that i -PrOH reacted more slowly than primary alcohols, 9 so we reasoned that it would minimize ester byproduct formation. Gratifyingly, in the presence of NaSPh, these conditions reduced byproduct formation to 6% of the ester ( 15c ), which was indeed readily separated from the elongated acid LYRAGLRAYP ( 15a , entry 5).…”
Section: Resultsmentioning
confidence: 99%
“…6,8 During this work, we found that the C-terminal residue is not epimerized during the modification reaction, even for sensitive residues such as His or Cys. 9 Therefore, we viewed this approach as ideal for backbone sequence diversification at the C terminus.…”
Section: Introductionmentioning
confidence: 99%
“…The Nbz/MeNbz technology has been successfully implemented in the preparation of glycoproteins-, phosphoproteins-, lipoproteins-, and cyclic proteins [32,[35][36][37][38][39][40][41][42][43][44]. In addition, this cleavable Nbz/MeNbz linker can undergo the attack of other nucleophiles rendering C-terminal modified peptides selectively labeled with different functionalities such as N-alkyl amides, esters, or cyclic peptides [45][46][47].…”
Section: N-acylurea Peptides As Thioester Surrogatesmentioning
confidence: 99%
“…To solve the problem of epimerization during carboxylate activation, many research groups have reported the use of various “linkers”, commonly Dbz, MeDbz, hydrazine, nitroindoline, etc . (Scheme C).…”
Section: Native Chemical Ligation (Ncl)mentioning
confidence: 99%